2016
DOI: 10.1007/s11064-016-1902-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Changes in Striatal Dopamine Transport in Preadolescent Rats Exposed Prenatally and/or Postnatally to Methamphetamine

Abstract: Methamphetamine (MA) is the most commonly used psychostimulant drug, the chronic abuse of which leads to neurodegenerative changes in the brain. The global use of MA is increasing, including in pregnant women. Since MA can cross both placental and haematoencephalic barriers and is also present in maternal milk, children of chronically abused mothers are exposed prenatally as well as postnatally. Women seem to be more vulnerable to some aspects of MA abuse than men. MA is thought to exert its effects among othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
0
5
0
2
Order By: Relevance
“…There are known differences in dopamine reuptake control, responses to amphetamines and DAT function between male and female rodents [37][38][39] . Furthermore, there are reports of sex differences in the behavioral and physiological effects of different DAT dysfunctions [40][41][42][43] . The strongest difference we observed was in the response to amphetamine of female DAT-Cre KI mice, which not only did not display amphetamine-induced hyperlocomotion, but indeed reduced their activity in response to the stimulant.…”
Section: Discussionmentioning
confidence: 99%
“…There are known differences in dopamine reuptake control, responses to amphetamines and DAT function between male and female rodents [37][38][39] . Furthermore, there are reports of sex differences in the behavioral and physiological effects of different DAT dysfunctions [40][41][42][43] . The strongest difference we observed was in the response to amphetamine of female DAT-Cre KI mice, which not only did not display amphetamine-induced hyperlocomotion, but indeed reduced their activity in response to the stimulant.…”
Section: Discussionmentioning
confidence: 99%
“…Methamphetamines are transported directly into the cell, and thus, neurotoxicity of methamphetamine is observed to be much higher as compared to cocaine. Furthermore, female animals seem to be more vulnerable to some aspects of methamphetamine abuse than males [32,33]. Recent human data seem to confirm the higher vulnerability of women as compared to men [34,35].…”
Section: Long-term Effect In Childrenmentioning
confidence: 96%
“…Sirova indicated that the combination of prenatal and postnatal METH exposure increases the risk of dopaminergic deficits by altering the activity of surface-expressed DATs, and that male mice were more sensitive. Additionally, changes in the fluidity of striatal membranes may significantly reduce the activity of surfaceexpressed DATs in female mice (Sirova et al, 2016). It should be noted that degeneration of dopaminergic neurons and monoamine neurotransmitter deficiency was observed in METH-exposed offspring (Salisbury et al, 2009).…”
Section: Behavioral Sensitization and Cross-sensitizationmentioning
confidence: 99%